2019
DOI: 10.1088/1742-6596/1366/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Navigation on Modified AOR Iterative Method in Static Indoor Environment

Abstract: One of the main issues when dealing with mobile robot navigation is that we have to resolve the obstacle avoidance problem, where when moving from a starting point to the goal point, the mobile robot will have to generate a collision-free path in order ensure that it can move efficiently in the environment. In this study, we attempt to resolve the issue by solving it iteratively via numerical technique. This solution is based on the potential field method that utilizes the Laplace’s equation to constrain the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Research in [14,39] utilized the MAOR scheme on their respective problems, and both concluded that this scheme produces the least number of iterations. Thus, this research proposes an MAOR scheme based on the fractional finite difference iterative method for solving the fractional Poisson equation (1).…”
Section: Fractional Finite Difference Methods With the Maor Schemementioning
confidence: 99%
“…Research in [14,39] utilized the MAOR scheme on their respective problems, and both concluded that this scheme produces the least number of iterations. Thus, this research proposes an MAOR scheme based on the fractional finite difference iterative method for solving the fractional Poisson equation (1).…”
Section: Fractional Finite Difference Methods With the Maor Schemementioning
confidence: 99%
“…Unlike the MAM method, which employs weighted parameters only, additional accelerated parameters are utilised for this newly proposed method. It can be constructed based on the AOR iterative scheme (15) to solve the given problem and is written as…”
Section: Red-black Modified Accelerated Arithmetic Mean (Maam) Methodsmentioning
confidence: 99%
“…Furthermore, it can be noted that the AOR can be treated as an extrapolation of the SOR method with overrelaxation parameter r and extrapolation parameter s = ω/r, as described in [12]. From Equations ( 13)- (15), u (k+1) denotes the unknown vector at iteration (k + 1), which we attempt to compute efficiently.…”
Section: Finite Difference Approximation Equationsmentioning
confidence: 99%
See 2 more Smart Citations